The poison squad : one chemist's single-minded crusade for food safety at the turn of the twentieth century - Blum, Deborah, 1954- (Penguin Press, 2018)
Dr. Harvey Washington Wiley set out to ensure food safety. He selected food tasters to test various food additives and preservatives, letting them know that the substances could be harmful or deadly. The tasters were recognized for their courage, and became known as the poison squad.